2018
DOI: 10.1111/dth.12786
|View full text |Cite
|
Sign up to set email alerts
|

Review of future insights of Dragon's Blood in dermatology

Abstract: To assess the possible clinical implication of Dragon's Blood in dermatology, a PubMed search was conducted using the keyword “Dragon's Blood,” “Croton lechleri,” and more. Dragon's Blood from C. lechleri is an Amazonian medicinal plant with a characteristic red sap. Its array of phytochemical action in preclinical studies include anti‐inflammatory, antioxidant, antimicrobial, antifungal, and antineoplastic properties. Clinical studies reflect wound healing and antiviral properties. Although its popularity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
(92 reference statements)
1
15
0
Order By: Relevance
“…It has been shown that during the development of a carcinoma, there is an increase in topoisomerases, because these enzymes are involved in cell replication [37]. Previous studies confirmed that mangiferin is capable of inhibiting the topoisomerase I enzyme (Topo I), involved in the splitting of DNA during cell division [38], Therefore, for this study, it was considered to evaluate its activity on Topo I in order to evaluate if there is loss of biological power or if it can be increased due to the controlled release of MG. Due to this, the used JN394 genetically modified strain (Matα ura3-52, leu2, trp1, his7, ade1-2, ISE2, rad52::LEU2) promotes a deficiency in the regeneration of DNA, greater permeability in the cell membrane y JN362a (Matα, ura3-52, leu2, trp1, his7, ade1-2, ISE2) resistant to DNA repair but sensitive to antimicrobial agents.…”
Section: Anti-topoisomerase Activitymentioning
confidence: 99%
“…It has been shown that during the development of a carcinoma, there is an increase in topoisomerases, because these enzymes are involved in cell replication [37]. Previous studies confirmed that mangiferin is capable of inhibiting the topoisomerase I enzyme (Topo I), involved in the splitting of DNA during cell division [38], Therefore, for this study, it was considered to evaluate its activity on Topo I in order to evaluate if there is loss of biological power or if it can be increased due to the controlled release of MG. Due to this, the used JN394 genetically modified strain (Matα ura3-52, leu2, trp1, his7, ade1-2, ISE2, rad52::LEU2) promotes a deficiency in the regeneration of DNA, greater permeability in the cell membrane y JN362a (Matα, ura3-52, leu2, trp1, his7, ade1-2, ISE2) resistant to DNA repair but sensitive to antimicrobial agents.…”
Section: Anti-topoisomerase Activitymentioning
confidence: 99%
“…Dracorhodin is originally the fruit extract of dragon blood, which can be used as a TCM (2,10). Dragon blood confers a number of bioactivities, including antibacterial, anti-diarrheal, anti-inflammatory, anti-oxidant, antitumor, anti-ulcer, antiviral, immune-modulatory and wound healing functions (1). Previous studies have demonstrated that dragon blood can promote the proliferation of fibroblasts, increase the ratio of cells in the S-phase of the cell cycle and collagen formation, in addition to enhancing wound healing (1,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Dragon blood confers a number of bioactivities, including antibacterial, anti-diarrheal, anti-inflammatory, anti-oxidant, antitumor, anti-ulcer, antiviral, immune-modulatory and wound healing functions (1). Previous studies have demonstrated that dragon blood can promote the proliferation of fibroblasts, increase the ratio of cells in the S-phase of the cell cycle and collagen formation, in addition to enhancing wound healing (1,11,12). In the present study, dracorhodin perchlorate was found to significantly promote wound healing in human HaCaT keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations